Pengaruh Penerapan Good Corporate Governance Terhadap Leverage dan Profitabilitas Pada Perusahaan Perbankan yang Terdaftar Di Bei Periode 2009-2013 - Tumewu, Riana Christel (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Since the economic crisis of 1997, the implementation of good corporate governance, or better known as the Good Corporate Governance (GCG) to issue raised in Indonesia. Due to poor corporate governance in Indonesia at that time, causing the economy to fall. So that everyone agrees to cover the difficulties Indonesia began with corporate governance. GCG or good corporate governance is a control mechanism to measure and manage the company, with the intention to improve corporate accountability. A good corporate governance (GCG) can be defined as a process and structure used by the organs of the company to enhance shareholder value. The purpose of this study was to (1) Testing and proving the influence of good corporate governance to leverage, (2) To test and prove the effect of the application of good corporate governance on profitability, (3) To test and prove the effect of leverage on profitability. The object of this research is the banking companies listed on the Stock Exchange. The data used in this study is data banking companies listed on the Stock Exchange as many as 16 samples according to criteria of the study, with the vulnerable period of the data used is year 2009-2013. The analytical method used is the analysis of the path. Results of data analysis using path analysis showed that the implementation of GCG Effect (X) to leverage (Y1) for the ratio of DER (Y1-DER) and DAR (Y1-DAR) is not significant. Different results are obtained when the GCG (X) showed a significant effect on profitability (Y2) for ROE (Y2-ROE) and NPM (NPM-Y2). As for the effect of leverage (Y1) to profitability (Y2) of the banking companies listed on the Stock Exchange tend to be varied. This means that the better the GCG implementation does not affect the banking company debt, but if the better implementation of GCG to profitability, it can enhance the company's ability to generate profits. Suggestions should the company become more motivated to implement GCG consistently in order to help improve the productivity and efficiency of a company that obviously affected the company's earnings that have an impact on investor confidence.